2012
DOI: 10.1371/journal.pone.0031908
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Therapeutic Efficacy of Mycobacterium smegmatis Expressing HBHA-hIL12 Fusion Protein against Mycobacterium tuberculosis in Mice

Abstract: Tuberculosis (TB) remains a major worldwide health problem. The only vaccine against TB, Mycobacterium bovis Bacille Calmette-Guerin (BCG), has demonstrated relatively low efficacy and does not provide satisfactory protection against the disease. More efficient vaccines and improved therapies are urgently needed to decrease the worldwide spread and burden of TB, and use of a viable, metabolizing mycobacteria vaccine may be a promising strategy against the disease. Here, we constructed a recombinant Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Mtb strain H37Rv was provided by the Institute of Drug and Biological Products Checking (Beijing, China) . Escherichia coli strain DH5a was provided by the Laboratory Animal Center of the Fourth Military Medical University (Xi'an, China), and was used for the expression of recombinant proteins Ag85B‐Hsp16.3, Ag85B, Hsp16.3, ESAT6, and CFP10.…”
Section: Methodsmentioning
confidence: 99%
“…Mtb strain H37Rv was provided by the Institute of Drug and Biological Products Checking (Beijing, China) . Escherichia coli strain DH5a was provided by the Laboratory Animal Center of the Fourth Military Medical University (Xi'an, China), and was used for the expression of recombinant proteins Ag85B‐Hsp16.3, Ag85B, Hsp16.3, ESAT6, and CFP10.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, these differential immune responses in TB patients versus healthy TBinfected subjects may suggest that an effective T cell response against HBHA could help to control M. tuberculosis replication and prevent disease development [54,62]. Interestingly, promising results were obtained in preclinical animal models, where immunization with HBHA was capable of eliciting levels of protective activity similar to those induced by BCG [54,55]; other studies provided further support of the role of HBHA as a candidate vaccine against TB [63,64]. Interestingly, it was found that intranasal immunization of mice with HBHA adjuvated with the cholera toxin induced an effective humoral and cellular immune response, and protection was measured as a reduction of the bacilli dissemination from the lung to the spleen [63].…”
Section: Hbhamentioning
confidence: 99%
“…18 We also demonstrated that the rMS strain expressing the fusion protein of heparin-binding hemagglutinin and human IL-12 (HBHA-IL-12) enhanced immunogenicity and improved Th1-type responses against TB, with the protective effects equivalent to that of the conventional BCG vaccine in mice. 19 Moreover, this rMS also decreased the bacterial load and pathological damage in lung of Mtb-infected mice. These results in aggregate suggest that rMS may exert potent immunological effects and enhance host immune responses against Mtb infections.…”
mentioning
confidence: 85%